Per una prosopografia del movimento mesmerista. Il progetto “Harmonia Universalis” - Armando, David; Belhoste, Bruno (Laboratorio dell'ISPF, 2015)
For a prosopography of the Mesmerist movement. The “Harmonia Universalis” project. The authors present the project “Base de données Harmonia Universalis: pour une prosopographie de la Société de l’Harmonie Universelle (1783-1786)”, funded by the Labex-Hastec programme. The project aims to reconnect, by returning to the sources, the various viewpoints (psychiatric, scientific, medical, politico-social...) which historians have applied to examine animal magnetism. A prosopography in the form of a data base of the members of the Society of Harmony will constitute the nucleus of an internet site dedicated to the doctrines and the practices introduced by Franz Anton Mesmer and will lead to a network analysis of the mesmerist moviment. The first results confirm the complexity of the vicissitudes of mesmerism and open new perspectives on its role in French society on the eve of the Revolution.